Smart traffic lights prototype system for pedestrians / Nor Dayana Athira Mohamad Toel - Mohamad Toel, Nor Dayana Athira (2022)
Recently, many deaths among pedestrians while crossing the road have increased drastically. This is due to their lack of awareness while crossing the street, mainly while waiting for the traffic light to turn green. Traffic lights that do not work properly are one of the many reasons for a pedestrian accident. This project aims to develop a system to reduce pedestrians death. The objectives consist of studying the existing project related to the smart traffic lights system, developing a prototype system based on Wireless Sensor Network, and evaluating the usability of a prototype system using PSSUQ. The preliminary survey was conducted to gather information about the study. 30 respondents were selected to answer all the questionnaires. The waterfall model was used to develop the prototype system. The Arduino platform and NodeMCU microcontroller were used when developing the prototype system for the Smart Traffic Lights Prototype System for Pedestrians. In order to evaluate the usability, the Post-Study System Usability Questionnaire was conducted to evaluate the usability based on 3 respondents. In order to evaluate the usability, the Post-Study System Usability Questionnaire results show that respondents were satisfied using the Smart Traffic Lights Prototype System for Pedestrians. In conclusion, the Smart Traffic Prototype System for Pedestrians was developed to send notifications to pedestrians while waiting for traffic lights to turn green and reduce pedestrians’ death.